Phytochemicals, Nutrient Levels and Antioxidants of Various Types of Sweet Potatoes (Ipomoea batatas L.) - Nurdin Rahman; Nurhanifah Muthmainnah Nurdin (Poltekita : Jurnal Ilmu Kesehatan, 2023)
This study aims to identify the phytochemical compounds, including flavonoids, tannins, phenols, beta-carotene, anthocyanins, and fiber, as well as the antioxidant capacity of various types of sweet potatoes. Method: The research followed a descriptive observational design with laboratory-based testing. The identification of phytochemical compounds utilized specific reagents. One Way ANOVA was employed to assess the differences in average levels of phytochemicals, nutrients, and antioxidant capacity (IC50) among the different types of sweet potatoes with normally distributed data. The determination of flavonoid, tannin, phenol, beta-carotene, and anthocyanin levels was carried out using UV/Vis Spectrophotometry at specific wavelengths. Crude fiber content was determined using the gravimetric method, while the antioxidant capacity was measured using the DPPH (2,2-Diphenyl-1-Picrylhydrazyl) method. Results: The findings indicated that all types of sweet potatoes contain alkaloids, while some lack steroids. Purple sweet potatoes showed the highest levels of flavonoids, tannins, and phenols at 627.27, 1727.27, and 1507.14 mg/100 g, significantly differing from other types of sweet potatoes (p = 0.00). Besides, purple sweet potatoes exhibited the highest anthocyanin content (18.35 mg/100 g) compared to other types, showing a significant difference (p = 0.00). Orange sweet potatoes exhibited the highest levels of beta-carotene and fiber, at 15.49 and 5.63 mg/100 g, respectively, although the difference was not statistically significant (p = 0.83). The antioxidant capacity (IC50) of purple, orange, white, and yellow sweet potatoes were 45.13, 266.59, 190.01, and 210.73 ppm, respectively. Conclusion: Different varieties of sweet potatoes exhibit variations in phytochemical composition and antioxidant capacity. Purple sweet potatoes are rich in flavonoids, tannins, phenols, and anthocyanins, with significant antioxidant potential. Orange sweet potatoes show high levels of beta-carotene and fiber but have comparable antioxidant activity to white and yellow varieties